Factor Analysis of The Level of Hand Hygiene Compliance Among Hospital Nurses in Indonesia: A Systematic Review - Ulfa, Maria; Adi, M. Sakundarno; Suryoputro, Antono (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2024)
One of the main patient safety goals is the prevention of nosocomial infections. Nurses have quite a big influence on the occurrence of nosocomial infections because their interaction with patients for 24 hours. An effective prevention effort that can be carried out by nurses is implementing standard hand hygiene. However, the incidence of nosocomial infections is observed to be high and many hand hygiene measures are still not carried out by nurses. This systematic review will provide an overview of the level of nurse compliance with the implementation of hand hygiene in hospitals in Indonesia as well as discussing the factors that can influence it. Search for articles using the Google Scholar database according to PRISMA, along 2019-2023 with predetermined inclusion and exclusion criteria. The final results in the form of 16 included articles and descriptive analysis show that the implementation of hand hygiene in several hospitals is not up to standard. Several factors influence the level of hand hygiene compliance among nurses, including attitude, knowledge, motivation, supervision, facilities, length of work, self-ability and workload. Among these factors, attitude shows the most promising influence on the level of hand hygiene compliance but this does not rule out the possibility of developing other factors in further research. Therefore, nurses compliance with the implementation of hand hygiene in hospitals in Indonesia still needs to be improved through improving the factors that influence it.